Combination of a novel heat shock protein 90-targeted photodynamic therapy with PD-1/PD-L1 blockade induces potent systemic antitumor efficacy and abscopal effect against breast cancers. Issue 9 (28th September 2022) - Kaneko, Kensuke; Acharya, Chaitanya R; Nagata, Hiroshi; Yang, Xiao; Hartman, Zachary Conrad; Hobeika, Amy; Hughes, Philip F; Haystead, Timothy A J; Morse, Michael A; Lyerly, Herbert Kim; Osada, Takuya
Abstract : Background: We previously demonstrated potent antitumor activity against human breast cancer xenografts using photodynamic therapy (PDT) targeting a novel tumor-specific photosensitizer (HS201), which binds heat shock protein 90 (HS201-PDT). However, induction of systemic antitumor immunity by HS201-PDT alone or by the combination strategy with immune checkpoint blockade has yet to be determined. Methods: Using unilateral and bilateral implantation models of syngeneic breast tumors (E0771, MM3MG-HER2, and JC-HER3) in mice, we assessed whether HS201-PDT could induce local and systemic antitumor immunity. In an attempt to achieve a stronger abscopal effect for distant tumors, the combination strategy with anti-PD-L1 antibody was tested. Tumor-infiltrating leukocytes were analyzed by single cell RNA-sequencing and receptor-ligand interactome analysis to characterize in more detailed the mechanisms of action of the treatment and key signaling pathways involved. Results: HS201-PDT demonstrated greater tumor control and survival in immune competent mice than in immunocompromised mice, suggesting the role of induced antitumor immunity; however, survival was modest and an abscopal effect on distant implanted tumor was weak. A combination of HS201-PDT with anti-PD-L1 antibody demonstrated the greatest antigen-specific immune response, tumor growth suppression, prolonged mouse survival time and abscopal effect. The most significant increase of intratumoral, activated CD8+T cells and decrease of exhausted CD8+T cells occurred following combination treatment compared with HS201-PDT monotherapy. Receptor-ligand interactome analysis showed marked enhancement of several pathways, such as CXCL, GALECTIN, GITRL, PECAM1 and NOTCH, associated with CD8+T cell activation in the combination group. Notably, the expression of the CXCR3 gene signature was the highest in the combination group, possibly explaining the enhanced tumor infiltration by T cells. Conclusions: The increased antitumor activity and upregulated CXCR3 gene signature induced by the combination of anti-PD-L1 antibody with HS201-PDT warrants the clinical testing of HS201-PDT combined with PD-1/PD-L1 blockade in patients with breast cancer, and the use of the CXCR3 gene signature as a biomarker.